2017
DOI: 10.7897/2230-8407.088141
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Cancer Potency and Sustained Release of Phytosomal Diallyl Disulfide Containing Methanolic Allium Sativum Extract Against Breast Cancer

Abstract: Vesicular drug delivery system like phytosomes is a widely adopted section of pharmaceutical inventions. It improves therapeu tic efficacies of drug by controlled and sustained action. It is also used to improve the therapeutic index, solubility, stability and rapid degradation of drug molecules. Phytosome is made of phytoconstituents of herbal extract that is surrounded and bounded by one or more concentric spheres of lipid layers. The purpose of this study is to synthesize an economical phytosome which will … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Other studies have shown that the method of producing phytosome can produce different entrapment efficiency values even though the ratio used is the same [32]. Nazeer et al, 2017 reported that garlic extract phytosomes made using the solvent evaporation method with a ratio of 1:1 produced an entrapment efficiency of 97.306% [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have shown that the method of producing phytosome can produce different entrapment efficiency values even though the ratio used is the same [32]. Nazeer et al, 2017 reported that garlic extract phytosomes made using the solvent evaporation method with a ratio of 1:1 produced an entrapment efficiency of 97.306% [11].…”
Section: Discussionmentioning
confidence: 99%
“…Compared with traditional herbal products, phytosomes can enhance the potency of the pharmacological effect because the medicinal ingredients are protected in the vesicle wall so that they are less likely to decompose [9,10]. Cancer treatment research using an ethanol extract of garlic in phytosomes showed that 100% of the phytosomes at 108.5 μg/ml are toxic to cancer cell lines (MCF 7) [11]. With the potential of allicin contained in a methanolic garlic extract, it is essential to formulate garlic extract phytosome to optimize the use of allicin in treating diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…Then the thin layer is re hydrated with water to form micelles. The phospholipid thin layer upon exposure with the water forms micelles that are then probe sonicated to achieve desired micelle size [9,[31][32][33].…”
Section: Phytosome Preparationmentioning
confidence: 99%
“…A clear analysis and scientific understanding of properties of the tumor, vascular modifications, and metastatic pathways have helped to develop the targeted drug delivery system [4]. Vesicular drug delivery system (VDDS) that includes liposomes, niosomes, ethosomes, aquasomes, and phytosomes is reported to be the ideal approach satisfying all the requirements for a targeting effective drug carrier [5][6][7][8][9]. VDDS are micelles made up of an aqueous core and generally lipid bilayer outer shell.…”
Section: Introductionmentioning
confidence: 99%